EFFECTS OF PRECONDITIONING, PLANT GROWTH REGULATORS AND KCL ON SHOOT REGENERATION OF PEANUT (ARACHIS HYPOGEA) - S. Day; M. Aasim2; A. Bakhsh (Journal of Animal and Plant Sciences, 2016)
Peanut (Arachis hypogeae) is an important legume used as green manure and cover crop also. In this study, preconditioned plumular apex explants with 20 mg L-1 BAP or unconditioned explants were cultured for 8 weeks on MS medium having 0.25-2.0 mg/l BAP with or without 0.25 mg L-1 NAA. 100 % shoot regeneration was recorded from both conditioned and unconditioned explants. However, conditioning of explants resulted in 1.5-2.0 fold more number of shoots per explants with relatively shorter shoots compared to unconditioned explants. Shoots per explant from unconditioned explants ranged 1.33-3.93 with 1.86-5.03 cm shoot length. Whereas, shoots per explant and shoot length of preconditioned explants ranged 2.73-5.87 and 0.77-1.75 cm respectively. In second experiment, 10, 15 and 20 µS/cm of KCl in combination with BA-NAA concentrations also resulted in 100 % shoot regeneration. Higher concentration of KCl imposed necrosis on the explants and generated shoots with low leaf area. Increased KCl concentration inhibited the shoots per explant but also enhanced the shoot length. In vitro regenerated shoots from both experiments were rooted successfully using IBA and acclimatized in the pots. Results revealed the superiority of preconditioning on shoot regeneration and KCl for shoot elongation.
Keywords: Preconditioning; in vitro; Necrosis; Peanut; Plumular apex